Polyglutamine expansion affects huntingtin conformation in multiple Huntington’s disease models - Manuel Daldin (Nature Portfolio, 2017)
Abstract Conformational changes in disease-associated or mutant proteins represent a key pathological aspect of Huntington’s disease (HD) and other protein misfolding diseases. Using immunoassays and biophysical approaches, we and others have recently reported that polyglutamine expansion in purified or recombinantly expressed huntingtin (HTT) proteins affects their conformational properties in a manner dependent on both polyglutamine repeat length and temperature but independent of HTT protein fragment length. These findings are consistent with the HD mutation affecting structural aspects of the amino-terminal region of the protein, and support the concept that modulating mutant HTT conformation might provide novel therapeutic and diagnostic opportunities. We now report that the same conformational TR-FRET based immunoassay detects polyglutamine- and temperature-dependent changes on the endogenously expressed HTT protein in peripheral tissues and post-mortem HD brain tissue, as well as in tissues from HD animal models. We also find that these temperature- and polyglutamine-dependent conformational changes are sensitive to bona-fide phosphorylation on S13 and S16 within the N17 domain of HTT. These findings provide key clinical and preclinical relevance to the conformational immunoassay, and provide supportive evidence for its application in the development of therapeutics aimed at correcting the conformation of polyglutamine-expanded proteins as well as the pharmacodynamics readouts to monitor their efficacy in preclinical models and in HD patients.